Peningkatan Kemampuan Public Speaking Bahasa Inggris bagi Mahasiswa Pascasarjana - Bastian, Arif Alexander; Gustianing, Defy; Yunianti, Eka Pratiwi; Ariyanti, Septika; Saidah, Siti; Mulati, Dyah Fitri (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
English public speaking skills are important skills that postgraduate students need to have, especially in facing international academic forums, such as seminars, conferences, and global residency activities. This community service activity aims to improve the English public speaking skills of postgraduate students at Aisyah Pringsewu University, especially from the Master of Midwifery and Master of Nursing study programs. The program is implemented online for eight weeks through a series of trainings that include basic communication theories, presentation techniques, public speaking exercises, and academic conference simulations. The implementation method includes identifying participant needs, compiling teaching modules, providing materials, individual and group practices, and feedback sessions. The results of community service related to public speaking training are an increase in students' oral communication skills by 11.9% based on the results of pre-test and post-test evaluations. In addition, the outputs produced in this training are the preparation of training modules, and the publication of scientific articles. This activity not only provides cognitive impacts, but also equips participants with the confidence to be better prepared to participate in international conferences, student exchanges, or global research collaborations that contribute to the academic image of the institution at the international level.